City of God = Cidade de Deus [videorecording (DVD)] - Salles, Walter; Ranvaud, Donald; Ribeiro, Andrea Barata; Ramos, Maurício Andrade; Mantovani, Bráulio; Lund, Kátia; Meirelles, Fernando; Rodrigues, Alexandre, 1983-; Firmino, Leandro, 1978-; Haagensen, Phellipe, 1984-; Silva, Douglas; Haagensen, Jonathan, 1983-; et al. (Miramax award-winning collection., 2003)
Built in the 1960s, Cidade de Deus (City of God) is a sprawling housing project built to keep the poor as far as possible from Rio's glamorous beaches and resorts. By the 1980s, it has degenerated into a war zone so dangerous that visitors from outside risk being shot to death on sight, a poisonous stew of poverty, drugs, and crime. "If you run away, they get you, and if you stay, they get you, too," says Rocket, who wants to be a photographer. Rocket's brother, friends, and neighbors begin with truck stick-ups, which lead to brothel hold-ups that lead to murder that leads to coke dealing that leads to street brawls with armies of gun-toting 11-year-olds. Soon a full-scale gang war rages in the City of God--understandably not covered by wary Rio photojournalists--but just the opportunity Rocket needs to make his move, get a job at a newspaper, and get out.